Compound effect : jumpstart your income, your life, your success - Darren Hardy (UK John Murray Learning, 2022)
As the central curator of the success media industry for over 25 years, author Darren Hardy has heard it all, seen it all, and tried most of it. This book reveals the core principles that drive success. The Compound Effect contains the essence of what every superachiever needs to know, practice, and master to obtain extraordinary success. Inside you will find strategies on:How to win--every time! The No. 1 strategy to achieve any goal and triumph over any competitor, even if they're smarter, more talented or more experienced.Eradicating your bad habits (some you might be unaware of!) that are derailing your progress.Painlessly installing the few key disciplines required for major breakthroughs.The real, lasting keys to motivation--how to get yourself to do things you don't feel like doing.Capturing the elusive, awesome force of momentum. Catch this, and you'll be unstoppable.The acceleration secrets of superachievers. Do they have an unfair advantage? Yes, they do, and now you can too! If you're serious about living an extraordinary life, use the power of The Compound Effect to create the success you desire. Begin your journey today!
Keywords: Motivation, morale, discipline